Comparison of impact of two decontamination solutions on the viability of the cells in human amnion - Smeringaiova, Ingrida; Trosan, Peter; Mrstinova, Miluse Berka; Matecha, Jan; Burkert, Jan; Bednar, Jan; Jirsova, Katerina (Cell and tissue banking, 2017)
Human amniotic membrane (HAM) is used as an allograft in regenerative medicine or as a source of pluripotent cells for stem cell research. Various decontamination protocols and solutions are used to sterilize HAM before its application, but little is known about the toxicity of disinfectants on HAM cells. In this study, we tested two decontamination solutions, commercial (BASE·128) and laboratory decontamination solution (LDS), with an analogous content of antimycotic/antibiotics for their cytotoxic effect on HAM epithelial (EC) and mesenchymal stromal cells (MSC). HAM was processed in a standard way, placed on nitrocellulose scaffold, and decontaminated, following three protocols: (1) 6 h, 37 °C; (2) 24 h, room temperature; (3) 24 h, 4 °C. The viability of EC was assessed via trypan blue staining. The apoptotic cells were detected using terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL). The mean % (±SD) of dead EC (%DEC) from six fresh placentas was 12.9 ± 18.1. Decontamination increased %DEC compared to culture medium. Decontamination with BASE·128 for 6 h, 37 °C led to the highest EC viability (81.7%). Treatment with LDS at 24 h, 4 °C resulted in the lowest EC viability (55.9%) in the set. MSC were more affected by apoptosis than EC. Although the BASE·128 expresses lower toxicity compared to LDS, we present LDS as an alternative decontamination solution with a satisfactory preservation of cell viability. The basic formula of LDS will be optimised by enrichment with nutrient components, such as glucose or vitamins, to improve cell viability.
Keywords: Cell Survival; kryoprezervace; Pregnancy; Humans; Cryopreservation; Amniotic membrane; Viability; koncové značení zlomů DNA in situ; Female; In Situ Nick-End Labeling; viabilita buněk; počet buněk; lidé; Cells, Cultured; dekontaminace; apoptóza; Decontamination; ženské pohlaví; Mesenchymal Stem Cells; mezenchymální kmenové buňky; kultivované buňky; Epithelial and mesenchymal cells; Amnion; těhotenství; Decontamination solution; Apoptosis; Cell Count; amnion